Application of native and phosphorylated tapioca starches in potato starch noodle - Muhammad, Kharidah; Kusnandar, Feri; Mat Hashim, Dzulkifly; Abd. Rahman, Russly (Wiley, 1999)
Characteristics of potato starch noodles substituted with native, phosphorylated and commercial phosphorylated (MTS283) tapioca starches were evaluated. Substitution of up to 17% with phosphorylated tapioca starch or up to 35% with MTS283 improved the quality of potato starch noodles. The resulting noodles were transparent and less brittle when uncooked, and were moderately elastic, less sticky and experienced lower cooking loss and less swelling when cooked. Substitution with native tapioca starch of up to 17% was also possible, but the uncooked noodles were less transparent and the cooked noodles swelled more and were less elastic.